2014
DOI: 10.1039/c4cc05307a
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature palladium-catalyzed direct 2-arylation of benzoxazoles with aryl and heteroaryl bromides

Abstract: An efficient room-temperature palladium-catalyzed direct 2-arylation of benzoxazoles with aryl bromides is presented. The Pd(OAc)2/NiXantphos-based catalyst enables the introduction of various aryl and heteroaryl groups, via a deprotonative cross-coupling process (DCCP) in good to excellent yields (75–99%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…9 Walsh et al demonstrated a productive room-temperature Pd(OAc) 2 / NiXantphos-catalyzed arylation reaction of benzoxazoles with aryl bromides. 10 Hoover et al synthesized a series of arylated benzoxazoles via the CuI-catalyzed oxidative coupling reaction of 2-nitrobenzoic acids and benzoxazoles. 11 Maiti et al…”
Section: Introductionmentioning
confidence: 99%
“…9 Walsh et al demonstrated a productive room-temperature Pd(OAc) 2 / NiXantphos-catalyzed arylation reaction of benzoxazoles with aryl bromides. 10 Hoover et al synthesized a series of arylated benzoxazoles via the CuI-catalyzed oxidative coupling reaction of 2-nitrobenzoic acids and benzoxazoles. 11 Maiti et al…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated NIXANTPHOS (L1) again showed enhanced reactivity over the structurally similar Xantphos (L2). [13][14][15][16][17] Regarding the palladium source, Pd(dba) 2 afforded higher AY (91% yield, entry 3) with NIXANTPHOS than Pd(OAc) 2 (78% yield, entry 1). [PdCl(allyl)] 2 and Pd(NCPh) 2 Cl 2 afforded good yields (80% and 79% respectively, entries 4 and 5), but lower than Pd(dba) 2. Our study of the palladium loading (Pd:NIXANT-PHOS 1:1.5) indicated that the yield increased to 95% (92% isolated yield, entry 6) at 5 mol% loading, but dropped to 45% at 2.5 mol% loading (entry 7).…”
mentioning
confidence: 99%
“…Given the success of deprotonative cross-coupling processes (DCCP) in the functionalization of a variety of weakly acidic sp 3 C–H bonds, 7 we envisioned application of this approach to the functionalization of substituted pyridines. 7q,u We recently reported the Pd(OAc) 2 /NIXANTPHOS-catalyzed DCCP of pyridylmethyl ethers to generate either arylated secondary ethers (Scheme 1A) or tertiary alcohols via tandem arylation/ [1,2]-Wittig rearrangement (Scheme 1B).…”
mentioning
confidence: 99%
“…7q,u We recently reported the Pd(OAc) 2 /NIXANTPHOS-catalyzed DCCP of pyridylmethyl ethers to generate either arylated secondary ethers (Scheme 1A) or tertiary alcohols via tandem arylation/ [1,2]-Wittig rearrangement (Scheme 1B). 7u Secondary aryl-(pyridyl)methanols (Figure 1) are also highly desirable but not accessible via the chemistry in Scheme 1A or B.…”
mentioning
confidence: 99%
See 1 more Smart Citation